Analisis Resepsi Pembaca terhadap Tema Novel Tenki No Ko Karya Makoto Shinkai - Iswahyudi, Agung; Anwar, Fithyani (HUMANIKA, 2025)
Readers play a crucial role in interpreting literary works, as each individual brings their own background and knowledge to the construction of meaning. Online platforms such as Goodreads.com and Bookmeter.com provide a space for diverse responses in the literature. This study aims to analyze reader responses to the themes in Tenki no Ko by Makoto Shinkai through a qualitative descriptive approach within the framework of Reception Theory, particularly Hans Robert Jauss's Horizon of Expectations. Data were collected from reviews of 60 online readers. The findings indicate that readers' expectations regarding three main themes–identity and freedom, love and sacrifice, and the relationship between weather and humanity–were largely fulfilled. These results highlight the connection between readers’ personal experiences and the thematic structure of the novel, offering insights into contemporary literary reception in digital environments.